Mathematical Simulation Analysis of Body Temperature Observations Covid-19 Patients - Ayly Soekanto; Emillia Devi Dwi Rianti; Endrayana Putut Laksminto Emanuel; Hardiyono Hardiyono (Jurnal Ilmiah Kedokteran Wijaya Kusuma, 2023)
At the end of January 2022 as many as 33 countries with new cases of 85% new variant called omicron which is the concern of the World Health Organization. Patients who have been diagnosed with COVID-19 are analyzed for temperature starting from the appearance of fever and until they experience recovery, followed by a decrease in body temperature and loss of fever. This study aims to conduct a mathematical simulation analysis of the observation of the body temperature of covid 19 patients. The research method is descriptive analysis by analyzing using mathematical simulations on the fever of covid 19 patients until the temperature changes to normal again. In February - March 2022, this research was carried out at the general practitioner clinic in Surabaya, Putat Gede, Sukomanunggal sub-district, with positive results from a swab examination and an infrared thermometer. The study population was patients with positive Covid-19 swab results, with a large study sample of 30 Covid-19 patients. The results showed that there was a mathematical simulation with a fever variation of 38 C. – 39.5 C occurs in covid 19 patients. The temperature is decreasing day by day approaching the normal body temperature according to the fever that is gone and healing occurs in Covid 19 patients.